BYCATCH AND DISCARD STUDY ON CATCHING DEVICES IN PRAPAT DISTRICT KABUPATENBENGKALIS VILLAGE, RIAU PROVINCE - Adjeng Fitriya Febriany; Alit Hindri Yani; Nofrizal Nofrizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACT A bycatch is another catch that is accidentally caught by the net. where the catch is unwanted or not the main target. Bycatch is usually dumped into the sea or used for human consumption or for livestock. This study aims to identify the composition and proportion of the main catch (main catch), bycatch and discarded catch in the stonet. The method used in this research is a survey method, namely by making direct observations in the field to see the catch of the grinding tool, then each catch is identified including the type of fish, the number of individual fish and the weight of the fish (primary data). Keywords:By-catch and discarded, stinging gear